Swertiamarin attenuates carbon tetrachloride (CCl4)-induced liver injury and inﬂammation in rats by regulating the TLR4 signaling pathway - Tao Wu; Qianrui Zhang; Hongping Song (Brazilian Journal of Pharmaceutical Sciences, 2019)
The aim of the present study is to illustrate the effects of swertiamarin (STM), a natural iridoid from herbal medicines, on hepatic inﬂammation induced by carbon tetrachloride (CCl4) in rats. Male Sprague Dawley rats were exposed to CCl4 with or without STM co-administration for 8 weeks. Our results revealed that STM administration (100 and 200 mg/kg b.w.) signiﬁcantly attenuated inflammation in livers of CCl4-treated rats. STM remarkably reduced the production of interleukin-1β (IL-1β), interleukin-6 (IL-6), tumor necrosis factor alpha (TNF-α), macrophage inflammatory protein-1a (MIP-1α), and monocyte chemotactic protein-1 (MCP-1) in liver tissue of CCl4-treated rats. In addition, STM treatment downregulated connective tissue growth factor (CTGF) and ser307pIRS-1 expression, which was induced by CCl4 exposure. In the process of exploring the anti-inflammatory mechanisms of STM action, we demonstrated that STM signiﬁcantly inhibited Toll-like receptor 4 (TLR4) and nuclear factor kappa B (NF-κB) p65 expression in the liver. In conclusion, these results suggested that the inhibition of CCl4-induced inﬂammation by STM was, at least in part, due to its regulation of the TLR4 /NF-κB signaling pathway.